Karpós: fruto do espírito - Lima, Weslei Cristiano [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Sonce de ancient times the jewel shows concepts, positions in the society and status of a person . These jewels are used in many civilizations as amulets and in some religions . This project consist in the making of three jewel pieces that's represents the complexe unity of the Lord and de fruit of the spirit (Gl. 5:22-23) through the search of the meaning of these words in the Hebraic scriptures (Tanakh) and the new alliance (B'rit Hadashah)

Desde a antiguidade as jóias externam conceitos, posições e status daqueles que as portam. Essas peças são usadas em muitas civilizações como amuletos peças religiosas. Este projeto consiste na confecção de três peças de joalheria que representam a complexa unidade do Eterno e os atributos do Espírito (Gl. 5:22-23) através da busca da etimologia desses atributos mostrados nas escrituras hebraicas (Tanakh) e na nova aliança (B'rit Hadashah)
Keywords: Joalherias; Judeus; Desenho industrial; Cultura